Pelatihan Pembuatan Biskuit Booster Asi Dan Perawatan Payudara Untuk Meningkatkan Volume Asi Ibu Menyusui: Training on Making Breast Milk Booster Biscuits and Breast Care to Increase Breast Milk Volume in Lactating Mothers - Dewiani, Kurnia; Himalaya, Dara; Suryati, Suryati; Destriyani, Sri Nengsih; Sari, Wenny Indah Purnama Eka (Chakra Brahmanda Lentera Institute, 2026)
The low coverage of exclusive breastfeeding in Mojo Rejo Village, Rejang Lebong Regency, is influenced by multiple factors, including limited maternal knowledge of lactation management, inadequate breast care techniques, and suboptimal nutritional intake during breastfeeding. This community service program aimed to implement research findings through an integrated training approach to increase breast milk volume and improve the success of exclusive breastfeeding. The program was conducted in the form of training sessions for breastfeeding mothers. The population included all breastfeeding mothers in Mojo Rejo Village, with a sample of 30 participants who attended and actively took part in the activities. The main variables addressed were knowledge of exclusive breastfeeding, skills in preparing breast milk booster biscuits, and skills in performing breast care. The instruments used consisted of educational materials, live demonstrations, and supporting teaching aids. The biscuit-making training utilized locally available ingredients, namely moringa leaf flour (Moringa oleifera) and tuna fish oil (Thunnus sp). The effectiveness of the program was assessed through participatory observation and skill evaluation. Data were analyzed descriptively to measure improvements in participants’ knowledge and practical skills. The evaluation results showed a 90% increase in participants’ knowledge regarding exclusive breastfeeding. In addition, there was a 70% improvement in participants’ skills in producing breast milk booster biscuits as an alternative supplementary food, and a 100% improvement in their ability to independently perform breast care practices. These findings indicate that the training successfully enhanced mothers’ capacity to optimize breast milk production. In conclusion, the integrated training program combining lactation education, breast care practice, and the preparation of locally sourced nutritional supplements was effective in improving breastfeeding mothers’ knowledge and skills. As a recommendation, similar mentoring and training models may be adopted by health workers and communities in other areas to address low breast milk production and exclusive breastfeeding coverage, while also empowering local communities through the utilization of local resources.